Analisis Faktor Penyebab Keterlambatan pada Proyek Konstruksi Pembangunan Tebing Sungai di Kota Sungai Penuh - Fernandez Elza; Waluyo Hatmoko (Jurnal Talenta Sipil, 2026)
Construction project delays remain common in Indonesia, particularly in infrastructure works located in regions with challenging geographical conditions, such as Sungai Penuh City, Jambi Province, which experiences high rainfall and mountainous terrain. This study aims to identify the factors causing delays in riverbank retaining wall projects and determine the most dominant factor. The research employed a mixed-method approach, combining qualitative in-depth interviews with seven respondents and quantitative analysis using the Analytical Hierarchy Process (AHP) to calculate priority weights, supported by secondary data from contract documents, project progress reports, and daily rainfall records. The Consistency Ratio (CR) value of 0.05 (